KI 2013: Advances in Artificial Intelligence 36th Annual German Conference on AI, Koblenz, Germany, September 16-20, 2013. Proceedings - Timm, Ingo J.; Thimm, Matthias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 35th Annual German Conference on Artificial Intelligence, KI 2013, held in Koblenz, Germany, in September 2013. The 24 revised full papers presented together with 8 short papers were carefully reviewed and selected from 70 submissions. The papers contain research results on theory and applications of all aspects of AI.
Using State-Based Planning Heuristics for Partial-Order Causal-Link -- Planning -- Workflow Clustering Using Semantic Similarity Measures -- Empathy and Its Modulation in a Virtual Human -- Cognitive Workload of Humans Using Artificial Intelligence Systems: Towards Objective Measurement Applying Eye-Tracking Technology.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Simulation and Modeling; User Interfaces and Human Computer Interaction; Mathematical Logic and Formal Languages